Low-Voltage-Ride-Through Control of a Modular Multilevel Single-Delta Bridge-Cell (SDBC) Inverter for Utility-Scale Photovoltaic Systems - Sochor P.; Tan N.M.L.; Akagi H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bridge circuits; Capacitors; Cascade control systems; Electric inverters; Feedforward control; Photovoltaic cells; Power quality; Quality control; Voltage control; Feedforward control methods; Grid fault conditions; Low voltage ride through (LVRT); Low-voltage ride-through; Medium voltage; Modular multilevel cascade inverters; Photovoltaic systems; Zero sequence current; Electric power system control